Literature review on Determinants Affecting Knowledge Sharing - Zarir Yusoff, Mohd; Saiful Izwaan Saadon, Mohd; Haqimin Salleh, Nurul; Kamaron, Tomingan; Ahmad, Hanafi (International Journal of Psychosocial Rehabilitation, 2020)
Knowledge sharing, which has been recognized as a part of knowledge management. It is defined as a willingness to share and to seek between two parties: knowledge seekers and knowledge owners. This action was held to warrant the organization to remain relevant and the continuity of knowledge to exist and evolve, regardless of the availability of the knowledge owner. This paper aims to understand the current determinants that contribute to the knowledge sharing intention among knowledge workers and identify potential future research from the literature review. The outcome from the findings will allow the researcher to determine the substantial factors from various determinants of personnel and organization. In addition, the outcome from the paper also aims at assisting the personnel from academia in finding the proper channel to reach the knowledge worker and hence gaining the respective knowledge that is beneficial to them from the port operator industry themselves.